Pemanfaatan Serai sebagai Spray Anti Nyamuk oleh Mahasiswa KKNT Bela Negara di Desa Gedangan - I Wayan Darma Batara; Natalia Dwi Wulandari; Roziana Febrianita (Institut Teknologi dan Bisnis Semarang, 2024)
Mosquito-borne diseases such as dengue fever, Zika, and malaria pose significant health threats in Indonesia, particularly in tropical areas like Gedangan Village, Jombang Regency. To reduce the risk of disease transmission, students of the Thematic Community Service Program (KKN) from Universitas Pembangunan Nasional